Female Liberation in John Fowles’ The French Lieutenant's Woman (Revista de Investigaciones Universidad del Quindío, 2023)
The researchers intend to analyze John Fowles’ The French Lieutenant's Woman to depict how the female protagonists reject the notion of being eunuchs and experience liberation and revolution within the social context. To carry out this study, the researchers analyze the female characters. This masterpiece revolves around the notions of love and sexuality. The French Lieutenant's Woman has been analyzed from different aspects of feminism. However, in this research, the purpose is to depict how Victorian women are able to break the phallocentric discourse by negating sexual differences and becoming eunuch subjects. The beginning of the novel shows Charles’ engagement with Ernestina mostly based on the social doctrines of the Victorian era. In fact, there is no love between them and what binds them together is social expectation. Ernestina is the symbol of a woman who desires to be a female eunuch and obey the principles of the nuclear family. On the other hand, Sarah is a rebellious character who selects love over the social doctrines of Victorian society. The present research is conducted based on Luce Irigaray and Germaine Greer's theories in which the role of Victorian women is analyzed.
Keywords: Female Liberation; Sexual Difference; Eunuch; Phallocentrism; Victorian Era; Male Discourse